Processos educativos nas práticas do brincar em uma casa de acolhimento - Portella, Camila de Carvalho Cordeiro (Universidade Federal de São Carlos, 2024)
In this master's research, we aimed to identify and understand the educative processes resulting from the social practice of children playing in a shelter in a city in the interior of São Paulo. This is a qualitative research, whose the data production was carried out based on participant observation, with mapping of routines and games, as well as holding a conversation circle, with records being made in a field diary. We held 21 meetings, which mainly included moments with children. For data analysis, we performed category coding. The results point to the analytical categories: playing to be more; oppressive relationships; affections shared, demanded, and denied; and role-play. Playing proved to be a social practice, from which various educative processes took place, such as collaboration, responsibility for household chores, dialogue, care for others, elaboration of conflicts, education of longing, acceptance, trust, affection, struggle for equality and rights, coexistence, amorousness, hope, respect, companionship and unity in diversity, proving to be a humanizing, liberating, dialogic activity that allows children to exercise themselves in being more, in being who they want to be, in going beyond dehumanizing situations and oppressors that marked their stories.

En esta investigación de maestría, nuestro objetivo fue identificar y comprender los procesos educativos resultantes de la práctica social de niños que juegan en un albergue de una ciudad del interior de São Paulo. Se trata de una investigación cualitativa, en que la producción de datos se realizó a partir de la observación participante, con mapeo de rutinas y juegos, así como la realización de un círculo de conversación, registrándose en un diario de campo. Se realizaron 21 reuniones, que incluyeron principalmente momentos con niños. Para el análisis de datos, realizamos codificación de categorías. Los resultados apuntan a las categorías analíticas: jugar para ser más; relaciones opresivas; afectos compartidos, exigidos y negados; y juego de roles. El juego resultó ser una práctica social, a partir de la cual se dieron varios procesos educativos, como la colaboración, la responsabilidad en las tareas, el diálogo, el cuidado de los demás, la elaboración de conflictos, la educación de la nostalgia, la aceptación, la confianza, el cariño, la lucha por la igualdad y los derechos, convivencia, esperanza, amorosidade, respeto, compañerismo y unidad en la diversidad, resultando ser una actividad humanizadora, liberadora, dialógica que permite a los niños ejercitarse en ser más, en ser quienes quieren ser, en ir más allá de situaciones deshumanizantes y sentimientos opresivos que marcaron sus historias.

Nella ricerca di questo master, abbiamo mirato a identificare e comprendere i processi educativi derivanti dalla pratica sociale dei bambini che giocano in una casa di accoglienza in una città dell'interno di São Paulo. Si tratta di una ricerca qualitativa, in cui la produzione dei dati è stata effettuata sulla base dell'osservazione partecipanti, con la mappatura di routine e giochi, nonché con lo svolgimento di un circolo di conversazione, con registrazioni effettuate in un diario sul campo. Si sono svolti 21 incontri che hanno previsto principalmente momenti con i bambini. Per l'analisi dei dati, abbiamo eseguito la codifica delle categorie. I risultati puntano alle categorie analitiche: giocare per essere di più; relazioni oppressive; affetti condivisi, richiesti e negati; e giochi di ruolo. Il gioco si è rivelato una pratica sociale, da cui hanno preso avvio diversi processi educativi, quali la collaborazione, la responsabilità dei compiti, il dialogo, la cura per gli altri, l'elaborazione dei conflitti, l'educazione alla nostalgia, l'accettazione, la fiducia, l'affetto, la lotta per l'uguaglianza e i diritti, convivenza, amorosità, speranza, rispetto, compagnia e unità nella diversità, rivelandosi un'attività umanizzante, liberatrice, dialogica che permette ai bambini di esercitarsi nell'essere di più, nell'essere chi vogliono essere, nell'andare oltre situazioni disumanizzanti e sentimenti oppressivi che li hanno segnati le loro storie.
Educative processes in playing practices in a children's shelter
Keywords: Processos educativos; Brincar; Crianças; Acolhimento institucional; Educative processes; To play; Children; Children's shelter; Procesos educativos; Jugar; Niños; Acogimiento institucional; Processi educativi; Giocare; Bambini; Accoglienza istituzionale; CIENCIAS HUMANAS::EDUCACAO; CIENCIAS HUMANAS::PSICOLOGIA